A Comparative Study of Blood Levels of Manganese, Some Macroelements and Heavy Metals in Obese and Non-Obese Polycystic Ovary Syndrome Patients - H. Mhaibes, Sarah; A. Taher, Mohammed; H. Badr, Ala; H. Badr, Ala (Iraqi Journal of Pharmaceutical Sciences, 2017)
Polycystic ovary syndrome (PCOS) is a prevalent condition in women of reproductive age. It is characterized by androgen excess and chronic anovulation. Some trace elements, macroelements, and heavy metals have been linked to pathophysiological mechanisms of PCOS . To study the alterations in the serum levels of the trace element manganese (Mn), some macroelements, magnesium(Mg) and calcium (Ca), and the heavy metals cadmium (Cd) and lead (Pb), in obese and non-obese PCOS patients; and the association of these alterations with some of the hormonal changes occurring in PCOS. The study was carried out at Kamal Al-Samarrai Hospital (Center for Infertility treatment and in vitro Fertilization "IVF") Baghdad- Iraq. Eighty-two women were enrolled in the study. Fifty-four of them were diagnosed by a specialist gynecologist as PCOS patients; they were subdivided into two subgroups according to their body mass index (BMI); twenty-seven obese PCOS patients with BMI > 30 kg/m2, and another twenty seven non obese patients PCOS with BMI <30 kg/m2. Whereas, twenty-eight apparently healthy women with regular menstruation and of comparable age, were selected to serve as control groups; they were subdivided into, fourteen obese women with BMI > 30kg/m2, and fourteen non obese women with BMI <30 kg/m2. Blood lead and cadmium levels were significantly higher in both of the obese and the non-obese PCOS groups, than in their corresponding control groups. While, serum magnesium, calcium and manganese levels were significantly lower in both of the obese and the non-obese PCOS groups, as compared to their corresponding control groups. The results revealed no significant difference in the levels of the measured elements, between the obese PCOS group and the non-obese PCOS group. The serum FSH levels was significantly lower in obese PCOS patients than in the obese and non-obese control groups. There was a positive correlation between blood lead and serum TSH levels in non-obese PCOS women; and between serum total testosterone and cadmium levels in obese PCOS women. Finally, there was negative correlation between serum magnesium and serum LH levels in non-obese PCOS women. the study has demonstrated higher blood levels of lead and cadmium; and lower serum levels of magnesium, calcium and manganese in PCOS groups than control subject. There were no significant differences between obese PCOS women and non-obese PCOS women in the levels of the studied hormones, elements and heavy metals.